Influence of chloride and pH on the pitting mechanism of Zn‐Ni alloy coating in sodium chloride solutions. (24th January 2021) - Anwar, Shams; Khan, Faisal; Caines, Susan; Abbassi, Rouzbeh; Zhang, Yahui
Abstract: This paper presents the pitting corrosion behaviour of Zn‐Ni alloy coatings in NaCl solutions with different chloride concentrations and pH. The pitting‐behaviour investigation is done using an optical microscope, potentiodynamic polarization (Tafel slopes), electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM) integrated with energy dispersive spectroscopy (EDS). The design of the experiment with three‐level fractional factorial design (FFD) is used to analyze the behaviour of pitting corrosion. The pitting behaviour in acidic solution with low chloride concentration was found to be significantly different from that in the neutral solution with high chloride concentration. Electrochemical analysis indicates that the corrosion behaviour of samples immersed at 0.35 moL/L NaCl and pH 3.0 at different exposure times have low impedance values compared to the 0.35 moL/L NaCl and pH 7.0 samples. SEM images show that the pH and chloride concentration in the electrolyte has a significant influence on the pitting morphology. Exclusive large pit morphology in an acidic solution (pH 3.0) with low chloride concentration (0.35 moL/L) was also observed. This provides new insight into pitting behaviour on a coated material. The study will serve a valuable tool toward designing or selecting metal coatings for marine or corrosive environments.